Pengambangan Instrumen Tes Literasi Kimia Materi Larutan Penyangga untuk Mendukung Tujuan Pembangunan Berkelanjutan (SDGs) 4: Pendidikan Berkualitas - iska Handa Yani; Yerimadesi; Fauzana Gazali; Riga (Jurnal Penelitian Pendidikan IPA, 2026)
Chemical literacy is a crucial 21st-century competence; however, its assessment instruments, particularly for buffer solution topics, remain limited. This Research and Development (R&D) study utilizing the Rasch model was conducted to develop a chemical literacy test instrument in support of SDGs 4: Quality Education. The test was developed from eight initial items and piloted on 72 senior high school students. Data analysis techniques included the Content Validity Index (CVI) and Ministeps software analysis. The content validity results yielded a CVI value of 0.96 (valid), and empirical analysis demonstrated that all eight items satisfied the item fit criteria. The instrument demonstrated a Cronbach's alpha of 0.83 (good), person reliability of 0.78 (fair), and item reliability of 0.90 (good). These data indicate an excellent person-item interaction, moderately stable student responses, and high instrument reliability. The item separation value (2.99) classified the item difficulty into four strata, while the person separation value (1.91) grouped student abilities into three strata. Although this instrument provides comprehensive psychometric quality to support SDGs 4 targets and assists teachers in measuring students' chemical literacy, future research is recommended to modify the instrument by incorporating more complex and challenging items to capture a broader spectrum of student abilities.